Government and political trust : the quest for positive public administration - Duncan, Grant, 1960- (New York : Routledge, 2024)
"If the government is a problem, what should be done about it? A new era of intervention has begun following a global pandemic, climate change and strategic rivalry - but will a better government emerge from this? Political turmoil and polarisation are causing people to question how well their societies are governed and how leaders conduct themselves, while urgent practical challenges are arising for public policy and administration. A deeper concern, then, is to re-examine the nature and problem of government itself. This study covers historically enduring dilemmas that will persist, as well as emerging issues such as climate change and artificial intelligence. It sets out core concerns that systems of government, of all kinds, must address. The wide diversity of political beliefs and constitutions calls for toleration in order to foster effective collaboration across types and levels of government. Each country, community and individual follows their own path, but we can all do something to help restore political trust and to raise standards of public administration. An essential guide for those seeking general and lasting principles of good government, including elected officials, civil servants, community leaders and students of politics and public policy"--
Introduction -- Government: Why is it a problem? -- Enduring dilemmas of government -- Progress, calamity and trust -- The crisis of belief -- Models of government today -- The big issues -- What now?
Keywords: Political science; Public administration; BUSINESS & ECONOMICS / Government & Business; POLITICAL SCIENCE / Government / General